Proposta Curricular para Educação infantil: (re) significando saberes docentes - Sobral, Elaine Luciana da Silva (2008)
The theory contemporary in the field of early children education, as well the legal discourse and official texts valid in our country point to the need for systematization of proposals pedagogic / curriculum in institutions, built and carried out by subjects that act as factor of assurance care quality. Quest us about what knowledge are required to teachers in developing a proposed curriculum for children education. Defined as an object of study, the knowledge teachers necessary for the development of a proposed curriculum for children education. As goals, assume: investigate teachers knowledge necessary for the development of a proposed curriculum in a Public Institution for children education and contribute to the (new) meaning on the part of teachers, knowledge needed to build a proposed curriculum for children education. Assuming the principles of the paradigm of qualitative research, we have developed a research institution of a children education Network Public Hall of Ceará-Mirim-RN, which serves children of four and five years old (preschool) with the participation of 17 teachers and two supervisory (teachers) that institution - subject of our research. Therefore, we have adopted the principles of action research, according to which the knowledge gained through research should build so shared / dialogue in the relationship between researcher and participants, what is the implementation of an effective action formative. As the search procedures developed observations no-teaching participants in the meetings and activities of the classroom; semi-structured interviews (individual and collective) with teachers and supervisors; analysis of school documents and participant observation in the seminars of studies reflective. The latter is implemented as key moments of speech and thought, and finally to (new) meaning of knowledge, the subject of the research-action. For these knowledge, the systematization of the register built was developed based on the principles of analysis of Content that guided us to the definition of two categories 1) knowledge teachers concerning conceptions of curriculum / proposed curriculum and 2) knowledge teachers concerning specifics of children education. From these were built subs representing thematings more specific and significant, among the many that emerged in the analysis: 1.1) Definitions of curriculum and curriculum proposal; 1.2) The subjects makers / implementing a curriculum / proposed curriculum; 1.3) elements constituting a curriculum / proposed curriculum for children education and 2.1) Functions of children education and conception of child; 2.2) The space of the play in the organization of routine. Under the intervention could significant advances with regard to (new) meaning of such knowledge from the subjects, with major disruptions to their original designs. These are presented and reflected in this work. In front of this movement, transformation, made the need for a permanent work in the context of the institution of in-service training, or mediated by pedagogical coordinator or other to assume this role with teachers, in order to provide the development and effectiveness of proposed curriculum consistent and contextualized in practice effective with the children concrete envisage the service to their specificities and a quality education